PROVIDING EXCLUSIVE ASI WITH THE LEVEL OF MOTHER'S KNOWLEDGE IN THE WORKING AREA OF THE KALUMATA PUSKESMAS - Linda Ahmad; Nurul Hidayati; Bambang Gunawan (Bajang Institute, 2025)
Exclusive breastfeeding means that the baby only receives breast milk. No other liquids or solid foods are given, not even water except oral rehydration solution, or vitamin, mineral or medication drops/syrups. A mother's low education means she is slow in adopting new knowledge, especially about matters related to breastfeeding patterns. The problem of providing exclusive breastfeeding is related to the low understanding of mothers, families and society about exclusive breastfeeding. This type of research is an analytical observational research type with a descriptive analytical quantitative research approach using a cross sectional design, data collection methods by distributing questionnaires to determine the mother's level of knowledge regarding exclusive breastfeeding. The research sample was mothers who had toddlers in the Kalumata Community Health Center Working Area, namely 92 respondents. Data analysis uses Chi-square and the next process only extends to looking for relationships (bivariate) using logistic regression. Based on the research results, variables that have a statistically significant relationship with nutritional status show the variable Exclusive Breastfeeding with the Mother's Knowledge Level in the Kalumata Community Health Center Working Area using the Chi-Square Test, namely (p value = 0.006). Suggestions for the Health Service: It is necessary to improve health programs that focus on peer group intervention, for example by establishing peer educators considering that peer factors also determine attitudes towards exclusive breastfeeding behavior